Hypertensive disorders of pregnancy: a manifestation of insulin resistance - Marandi, Satyabhama; D., Surya; Chanania, Kabita; Pati, Tapasi; Nayak, Sibananda; Jacob, Anju Mariam; Kumar R., Praveen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy is a unique physiological diabetogenic state characterised by increased insulin resistance that ensures adequate supply of nutrients to the developing fetus. The insulin sensitivity falls to upto 50 percent in the late pregnancy. Thus insulin resistance and the resultant hyperinsulinemia are the characteristics features that are evident in the normal pregnancy during third trimester. In Hypertensive disorders of pregnancy (HDP), there is exacerbation of the physiological insulin resistance that occurs in normal pregnancy resulting in increased fasting serum insulin level. Methods: This is a case control study conducted on 90 antenatal women, during the study period of one and half years (from December 2020 to June 2022) in IMS and SUM Hospital, Bhubaneswar. With informed written consent and after fulfilling the criterias, 60 normotensive patients were chosen as controls and 30 pregnant patients with hypertensive disorders of pregnancy were chosen as cases. After 8 hours of overnight fasting, 2ml of blood is drawn and processed by CMIA technology to detect fasting serum insulin levels. The mean fasting serum insulin levels were compared between the cases and the controls. Results: The mean fasting serum insulin level of controls was found to be 9.27 and the mean fasting serum insulin level of cases was found to be 15.01 which was higher than controls. This was found to be statistically significant with a P value of 0.000. Conclusions: Increased fasting serum insulin level is observed in women with HDP than normotensive pregnant women.